Effectiveness of Mechanical Treatments (Periosteal Stripping VS Non-Periosteal Stripping) on Fracture Healing: In Vivo Study - Nefihancoro, Udi Heru; Septriarta Parlindungan; Ida Bagus Budhi Surya Adnyana (HM Publisher, 2024)
Background: Periosteal stripping (PS) is a controversial technique in fracture management, with studies reporting both positive and negative effects on bone healing. This study aims to evaluate the effectiveness of PS and non-periosteal stripping (NPS) on fracture healing in the Sprague Dawley rat model. Methods: This study is an in vivo experimental research. Male Sprague Dawley rats (8-10 weeks old) were divided into four groups (n=10 per group): Group I: NPS, evaluation day 14; Group II: PS, evaluation day 14; Group III: NPS, evaluation day 28 and Group IV: PS, evaluation day 28. A standard fracture was created in the tibia, and PS or NPS was performed. Radiographic evaluation was performed on days 14 and 28, with the RUST score (Radiographic Union Score for Tibia) used to assess fracture healing. Statistical analysis was performed using the Kruskal-Wallis test. Results: The RUST score showed better fracture healing in the NPS group compared to PS on day 28 (p<0.05). There was no significant difference on day 14 (p>0.05). Conclusion: NPS was more effective in accelerating fracture healing in Sprague Dawley rats than PS, especially in the later stages of healing. These findings provide further evidence of the potential adverse effects of PS and highlight the importance of considering time in assessing its efficacy.